2011
DOI: 10.1111/j.1529-8019.2010.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal injection of PPD as a novel approach of immunotherapy in anogenital warts in pregnant women

Abstract: Immunotherapy for treatment of recalcitrant warts was used through different modalities including intralesional injection of purified protein derivative (PPD), which is an extract of Mycobacterium tuberculosis, used for testing exposure to tuberculin protein, either from a previous vaccination or from the environment. This method is used to evaluate the efficacy of a new approach of intradermal injection of PPD in the treatment of anogenital warts in pregnant women. A total of 40 pregnant women, aged 20-35 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
3
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 29 publications
5
53
3
3
Order By: Relevance
“…21 The higher clearance rates with imiquimod in our study may have been the result of needle-prick trauma during concomitant injection of the vehicle, which may have added to the inflammation and enhanced the immune response induced by imiquimod, 5%. There are several reports on the use of intralesional antigen and vaccine therapies in cutaneous warts, but none of them was a double-blind randomized trial, and only 3 studies 3,13,22 looked at the effect of these therapies on AGWs. A retrospective analysis 22 There was no statistically significant difference in percentage resolution at any point except at week 4, when the imiquimod, 5%, cream group showed a higher percentage of resolution compared with the Mw group.…”
Section: Discussionmentioning
confidence: 97%
“…21 The higher clearance rates with imiquimod in our study may have been the result of needle-prick trauma during concomitant injection of the vehicle, which may have added to the inflammation and enhanced the immune response induced by imiquimod, 5%. There are several reports on the use of intralesional antigen and vaccine therapies in cutaneous warts, but none of them was a double-blind randomized trial, and only 3 studies 3,13,22 looked at the effect of these therapies on AGWs. A retrospective analysis 22 There was no statistically significant difference in percentage resolution at any point except at week 4, when the imiquimod, 5%, cream group showed a higher percentage of resolution compared with the Mw group.…”
Section: Discussionmentioning
confidence: 97%
“…Antigens such as mumps, candida, trichophyton, Bacillus Calmette-Guerin, and PPD tuberculin were tried in different studies [15][16][17][18][19][20][21][22][23][24][25][26]. The mechanism of action of immunotherapy is still unclear as the human papilloma virus (HPV) antigen is usually produced in upper epithelial cells and is not exposed to antigen-presenting cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…PPD, tuberculin, was used in many studies as an immunotherapy [15][16][17][18][19][20][21]. The number of injections varied from 3, 4, 6, to 12 injections at 2-4-week intervals, with success rates ranging from 58.8 to 96%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro experiments have demonstrated that Candida has a proliferative effect on T-cells and that the cytokine most frequently produced by Langerhans cells exposed to Candida was interleukin 12, which promotes T-cell response (56,57). Intriguingly, injecting the wart, which is the site of active infection, may not be necessary to induce T-cell responses, as one group reported that weekly intradermal injections of PPD in the forearms was effective in treating anogenital warts in pregnant women (58). Additional evidence of de novo immune stimulation was demonstrated in our clinical trial of the HPV therapeutic vaccine mentioned above (33).…”
Section: De Novo Immune Stimulationmentioning
confidence: 99%